Alignment between genetic and physical map, and pheromone functions in Gibberella zeae - Lee, Jungkwan (Kansas State University, 2008)
Gibberella zeae is an ascomycete filamentous fungus and the major cause of Fusarium head blight, also called scab, in small grains. This dissertation contains three related studies of G. zeae. In the first, the genetic map was aligned with the first assembly of the genomic sequence released by The Broad Institute (Cambridge, MA). Approximately 99% of the sequence was anchored to the genetic map, indicating the high quality of the sequence assembly and validity of the genetic map. The alignments grouped the linkage groups and supercontigs into four sets, which is consistent with the hypothesis that there are four chromosomes in this fungus. In the second, the sex pheromone precursor genes (ppg1 and ppg2) and the pheromone receptor genes (pre1 and pre2) were identified and characterized. Deletion of ppg1 or pre2 ([Delta]ppg1 or [Delta]pre2 strains) reduced the number of perithecia produced by self-fertilization, but did not completely block perithecial formation. The proportion of crosses resulting from outcrossing increased when the [Delta]ppg1 strains were used as the female in crosses with male strains containing an intact ppg1 gene. [Delta]ppg2 and [Delta]pre1 mutants had no discernable effect on morphological phenotype or self-fertilization. Thus, one of the pheromone/receptor pairs (ppg1/pre2) found in many Ascomycetes has a role in, but is not essential for, selfing or outcrossing in G. zeae, whereas the other pheromone/receptor pair (ppg2/pre1) no longer has a detectable function in sexual reproduction. In the third study, spore germination of G. zeae was tested in the presence of α- factor-like pheromone peptides of G. zeae or N. crassa. The pheromone peptide of N. crassa more efficiently inhibited spore germination than did the peptide from G. zeae. Arginine and lysine residues were the most important determinants in blocking spore germination. In conclusion, this research has validated the genetic map and the genomic assembly of G. zeae, characterized sex pheromone functions and characterized pheromone peptide ability to inhibit spore germination. The pheromone peptides of G. zeae and N. crassa may be useful as control agents for G. zeae and pheromone peptide efficacy might be further enhanced by judicious substitutions for some of the amino acids.
Keywords: Gibberella zeae; Pheromone; Genetic map; Genome sequence; Germination inhibition; Peptide; Agriculture, Plant Pathology (0480)